Book Review: Rural Education for the Twenty-First Century: Identity, Place, and Community in a Globalizing World - Arlie Woodrum (Journal of Research in Rural Education, 2011)
When early last year a high-ranking official from the federal Department of Education visited us in New Mexico, I was invited to act as one of his guides, to set up a tour for him at two schools. With the dramatic infusion of Race to the Top funds into education, and in particular into states like New Mexico where achievement data have consistently indicated that our students rank near the bottom nationally, his stated goal was to understand better the challenges we face. With the collaboration of an urban principal, we hosts were soon able to arrange for our guest to tour an ethnically diverse, low SES elementary school in Albuquerque. But we also wanted our guest to get a sense of rural education in the state. Arranging for that, however, required more planning, for I wanted the official to get an overview, not just of a particular rural school, but a sense of New Mexico's ethnic, linguistic, and geographic complexity.